Genetic variations of Lansium domesticum Corr. accessions from Java, Sumatra and Ceram based on Random Amplified Polymorphic DNA fingerprints - KUSUMADEWI SRI YULITA (Biodiversitas Journal of Biological Diversity, 2011)
Yulita KS (2011) Genetic variations of Lansium domesticum Corr. accessions from Java, Bengkulu and Ceram based on Random Amplified Polymorphic DNA fingerprints. Biodiversitas 12: 125-130. Duku (Lansium domesticum Corr.) is one of popular tropical fruits in SE Asia. The species has three varieties, known as duku, langsat and kokosan; and duku is the most popular one for being the sweeties fruit. Indonesia has several local varieties of duku, such as duku Condet, duku Sumber and duku Palembang. This present study aimed toassess genetic diversity of 47 accessions of duku from Java, Sumatra, and Ceram based on RAPD fingerprints. Ten RAPD’s primers were initially screened and five were selected for the analysis. These five primers (OPA 7, 13, 18, OPB 7, and OPN 12) generated 53 scorable bands with an average of 10.6 polymorphic fragments per primer. Percentage of polymorphism ranged from 16.89% (OPA 7 and OPN 12) to 24.54% (OPB 7) with an average of 20.16% polymorphism. OPB 7 at 450 bp was exclusively possessed by accession 20 (Java), OPA 18 at 500 bp was by accession 6 (Java), 550 bp by 3 clones from Bengkulu. While OPN 12 at 300 bp and OPA 13 at 450 bp were shared among the accessions. Clustering analysis was performed based on RAPD profiles using the UPGMA method. The range of genetic similarity value among accessions was 0.02-0.65 suggesting high variation of gene pool existed among accessions.